Sport sparks: Supporting creative thinking by professional coaches - Lockerbie, J.; Maiden, N.; Wolf, A.; Zachos, K. (Proceedings of the 9th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2021)
This short paper reports a new digital tool that supports creative idea generation about possible solutions to these challenges. Exploratory design research resulted in a new digital tool that was designed for use by the coaches of elite athletes, to discover creative ideas with which to remove, overcome and mitigate the effects of concrete athlete under-performance. Furthermore, initial feedback from 22 professional sports practitioners revealed that use of the tool led to most of them understanding the challenge from new perspectives, exploring alternative options to solve the challenge, and influenced their decision-making about the challenge.